Dominasi Elit Lokal dalam Tata Kelola Perhutanan Sosial di Nagari Paru Kabupaten Sijunjung Sumatera Barat - Suryaningsih; Doni Hendrik (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2026)
This study examines the dynamics of local elite power in the governance of social forestry in Nagari Paru, Sijunjung Regency, West Sumatra. Despite having obtained a Social Forestry Decree (SK) since 2014 and having a tradition of jungle prohibition as a form of local wisdom in forest conservation, its implementation has not been effective. This study aims to analyze how local elite power, particularly the dominant role of the Village Head (Wali Nagari), influences the governance of the forest management institution (LPHN) and community participation. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation as well as data validation using source triangulation. The results show that the power structure in Nagari Paru is centralized. The dominant role of the village head has a strong influence on the governance of the Village Forest Management Institution (LPHN) and the level of community participation in the social forestry program in Nagari Paru.